On the use of wind direction fieid for the estimation of wind speed field - SHAIKH, Z. E.; DATTA, R. K. (MAUSAM, 1973)
This paper describes an objective scheme to estimate wind speed from the available isogonal field in the interior region and wind speed and direction for the boundary region. As a first step, the mean monthly wind field is taken as a guess field for the interior region. The divergence field is then computed, which along with the wind direction for the interior region is used to improve the guess field in successive scans, so as to match it with a the wind field along the boundary. This method has been tested over central India, a region of good conventional network. The results of the scheme which has potential advantages for augmenting data in otherwise sparse data region, is discussed.